AIpreneurship: Membangun Kewirausahaan Berbasis Kecerdasan Buatan di Era Digital Bagi Mahasiswa - Prameswara, Yosep Tegar (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
This study discusses the potential of AIpreneurship - the integration of artificial intelligence (AI) into entrepreneurial practices - to help students use digital technology as a strategic tool in entrepreneurship. Amidst the economic challenges of the post-COVID-19 pandemic, AI technology is emerging as an innovative solution that can improve efficiency, accelerate decision-making, and facilitate product innovation. In this context, students can not only enhance their entrepreneurial skills, but also gain the confidence to start new competitive ventures in the digital age. Through a systematic literature review, this study identifies the benefits of AIpreneurship as well as the implementation challenges, such as limited access to technology and high costs. The findings are expected to increase the understanding of AIpreneurship among university students and provide recommendations for educational institutions to support the adoption of AI in entrepreneurship education.